A Naturalistic Evaluation of a Group Intervention for Parents of Youth with Substance Use Disorders. Issue 3 (2nd July 2020) - Ameral, Victoria; Yule, Amy; McKowen, James; Bergman, Brandon G.; Nargiso, Jessica; Kelly, John F.
ABSTRACT: Parents of youth with substance use disorders (SUDs) often play a vital role in successful treatment, yet little is known about interventions designed to help them cope with the stress of this role, especially as delivered in real-world settings. Evaluations of such interventions could potentially inform adaptations to enhance their clinical utility. Parents of youth with SUDs attending a clinician-led group based on the CRAFT model completed measures at intake, 4- and 8-weeks. Parents ( n = 545) attended an average of 3.7 sessions; 12% completed all 8 weeks. Analysis of demographic predictors of retention indicated that older parents attended more sessions on average. Overall stress did not change across time points ( p > .05). However, parents reported improvement in parent empowerment as measured by the Parent Empowerment Scale, a novel measure of parent empowerment in coping with their child's SUD ( p < .001). Clinician led evidence-informed group services may improve parents' perceived ability to help their child with their SUD. Low retention rates highlight the need to better understand the factors contributing to retention, and the potential value of adaptations to shorten the intervention. Programs serving youth with SUDs may wish to consider integrating such group services to support parents.